The Influence of Investment and Managerial Ownership on Firm Value on Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange - Lihard Stevanus Lumapow (AIBPM Publisher, 2018)
This study aims to examine and analyze the effect of investment on firm value, as well as the influence of non-monotonic managerial ownership on firm value. This study uses a sample of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) from 2012 to 2016. The technique of collecting data is panel data (Time Series and Cross sectional), while the sampling technique used is purposive sampling. The data analysis method used is panel data regression with a random effect model (REM) approach. Based on the test results indicate that investment has a negative and not significant effect on firm value. Managerial ownership has a positive and significant influence on firm value, while squared managerial ownership has a negative but not significant effect on firm value. The results of this study have a non monotonic relationship between managerial ownership and firm value even though it is not significant. Keywords: Agency Theory, Firm Value, Investment, Managerial Ownership